(untitled) (Journal of Economic Research & Business Administration, 2016)
The paper emphasizes the issue of comprehensive research of gender aspects of management by scientists in this field. A direct interrelation between management and entrepreneurship and the relevance of their common study are substantiated. The main objective of the paper is research of management effectiveness of both genders representatives in Kazakhstan companies. A new material on the researched topic is generalized: a comparative analysis of performance of managerial functions, linking processes and leadership of female- and male-managers. In conclusion the applied recommendations are cited dedicated to employment of females and males for positions required the exercise of certain managerial functions and linking processes.